Selection of bacterial isolates with fungal inhibition against alfalfa phytopathogens to constitute a bacterial consortium - Moreno, María Valeria; Arolfo, Valeria; López, José Luis; Erdozain, Sofía Agostina; Bigatton, Ezequiel Darío; Ayoub, Ibrahim; Lucini, Enrique Iván; Lagares, Antonio; Odorizzi, Ariel (2024)
H INDEX: 11. Guía de la Biblioteca de la Universidad de Huelva: Evaluación de la Investigación: Índice H. https://guiasbuh.uhu.es/c.php?g=655120&p=4605523